2024
DOI: 10.1111/jerd.13193
|View full text |Cite
|
Sign up to set email alerts
|

Clinical performance of two ion‐releasing bulk‐fill composites in class I and class II restorations: A two‐year evaluation

Eman H. Albelasy,
Hamdi H. Hamama,
Hooi Pin Chew
et al.

Abstract: ObjectivesThis randomized clinical trial evaluated and compared the 2‐year clinical performance of two ion‐releasing bulk‐fill composites (Cention N and Surefil One) with that of a conventional bulk‐fill resin composite (Powerfil) in Class I and II cavities.MethodsThirty‐two patients, each with 3 Class I and/or Class II cavities under occlusion, were enrolled in this trial. A total of 96 restorations were placed, 32 for each material, as follows: a self‐adhesive composite; Surefil‐one, alkasite; Cention N, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 58 publications
1
8
0
1
Order By: Relevance
“…The ability of alkasite to meet the ISO requirement for minimum FS even under such unfavorable conditions indicates its optimal mechanical stability and potential for use in load-bearing areas. This is consistent with reports of alkasite’s good performance under clinical conditions, albeit with short follow-up times of only 1–2 years [ 13 , 14 , 15 , 16 , 17 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The ability of alkasite to meet the ISO requirement for minimum FS even under such unfavorable conditions indicates its optimal mechanical stability and potential for use in load-bearing areas. This is consistent with reports of alkasite’s good performance under clinical conditions, albeit with short follow-up times of only 1–2 years [ 13 , 14 , 15 , 16 , 17 ].…”
Section: Discussionsupporting
confidence: 92%
“…Some compositional differences among these material versions are likely but have not been explicitly stated by the manufacturer. Regardless of the material version, there is a reasonable amount of evidence for the good performance of the alkasite under in vitro conditions [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ], as well as in randomized clinical trials [ 13 , 14 , 15 , 16 , 17 ], as summarized below.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, 29 RCTs [ 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 ] were included, of which only 1 [ 50 ] was parallel. All studies reported that the total number of patients ranged from 10 to 92 and the number of teeth treated ranged from 16 to 180.…”
Section: Resultsmentioning
confidence: 99%
“…As with any new material, clinical and in vitro studies to test the biological, mechanical, durability, and optical properties were evaluated. Multiple clinical studies found Surefil one to be promising [ 7 , 10 , 11 ]. According to Lohbauer and Belli’s evaluation, Surefil one’s mechanical characteristics fell within a range that was comparable to that of the resin-based composites when compared to three direct composite resins and two GIC materials.…”
Section: Introductionmentioning
confidence: 99%